Synthesis of yttrium aluminum garnet ceramic powder doped with ruthenium - V.E. Suprunchuk; A.A. Kravtsov; L.V. Tarala; E.V. Medyanik; F.F. Malyavin; V.A. Lapin; D.P. Bedrakov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
In the course of the work, samples of ceramic powders of yttrium-aluminum garnet doped with ruthenium ions were obtained. The introduced amount of ruthenium was 5 and 10 wt.%, respectively. The annealing temperatures were 1150 and 1600°C. In the course of the work, changes in the morphology of ceramic powders of yttrium-aluminum garnet doped with ruthenium ions were considered using scanning electron microscopy. The elemental composition was studied using energy-dispersive spectroscopy. The phase composition was investigated by X-ray phase analysis. The specific surface area of the ceramic powder was estimated using the Brunauer-Emmett-Teller method. For the obtained samples, an increase in the specific surface area of the ceramic powder with a decrease in the quantitative content of ruthenium in the system was revealed. The presence of impurity phases was established for all samples. It was found that increasing the calcination temperature to 1600°C led to a decrease in the quantitative content of impurity phases, but did not lead to their complete elimination. The sample with the closest to a single-phase composition was obtained with a ruthenium content of no more than 5 wt.% in the material. The results obtained using differential thermal analysis showed that the ruthenium content in the amounts used does not affect the kinetics of phase transitions, as well as the kinetics of mass loss of the precursor powders.